Left- versus right-handed badminton slice shots: opposite spinning of the chiral shuttlecock and Magnus effect - Collet, Eric (Comptes Rendus. Physique)
The chiral nature of a badminton shuttlecock is responsible for its counter-clockwise spinning as it naturally propagates through the air. This induces a dissymmetry between left- and right-handed players and the resulting trajectories of the shuttlecock, which were captured in real condition on the badminton court in slow motion at 3700 fps. The videos clearly evidence this dissymmetry as slice shots performed by right-handers induce a natural counter-clockwise spinning, while the ones performed by left-handers induce a clockwise to counter-clockwise spinning, making trajectories of shuttlecocks different. The slow motion videos also caught a brief Magnus effect, often neglected in badminton, lifting up the shuttlecock for both left-handers and left-handers and affecting the effectiveness of the slice shot.